Urgensi Jurnalistik Islam dalam Dakwah di Media Baru - Fitri, F (Journal of Islamic Studies and Humanities, 2017)
The growth of mass media over time continues to grow and complex. The use of the term journalism or the press also continues to expand to include a broader meaning. Advances in communication technology create new journalism. Press or journalism with new media/internet is a channel of information dissemination that is effective and efficient. Islamic Journalism is part of national journalism in general. The presence of Islamic journalism other than as an agent of information dissemination and educators is dawah using writing. This article reviews the role of Islamic Journalism as a dawah in new media. The author analyzes the contents of the news text by taking samples on the Islamic sites are eramuslim.com and islampos.com. The result is both the site eramuslim.com and islampos.com can apply Islamic journalism, but less emphasize open attitude to the differences of understanding.* * *Pertumbuhan media massa dari waktu ke waktu terus berkembang dan kompleks. Penggunaan istilah jurnalisme atau pers juga terus berkembang mencakup makna yang semakin luas. Kemajuan teknologi komunikasi menciptakan jurnalisme baru. Pers atau jurnalisme dengan media baru (internet) merupakan saluran penyebaran informasi yang cukup efektif dan efisien. Jurnalistik Islam merupakan bagian jurnalistik nasional pada umumnya. Kehadiran jurnalisme atau jurnalistik Islam selain sebagai agen penyebar informasi, dan pendidik merupakan dakwah dengan tulisan. Artikel ini mengulas Peran Jurnalistik Islam sebagai dakwah di media baru. Penulis menganalisis isi teks berita dengan mengambil sampel pada situs Islam yaitu eramuslim.com dan islampos.com. Hasilnya baik situs eramuslim.com dan islampos.com dapat menerapkan jurnalistik Islam, namun kurang menonjolkan sikap terbuka bagi perbedaan paham.